Design of Multilevel Storage Medium through Sb2Te3/Ga2Sb3 Phase-Change Heterostructure. (1st February 2023) - Gu, Han; Wu, Weihua; Zhou, Xiaochen; Zhang, Pei; Fu, Bowen; Zhu, Xiaoqin
Abstract : The phase-change heterojunction Sb2 Te3 /Ga2 Sb3 thin films with different thickness ratios and periods were designed and prepared by the magnetron sputtering technique. The multi-level resistance states of phase-change heterojunction Sb2 Te3 /Ga2 Sb3 film were investigated from the perspective of material and device. As for the constant thickness ratio, both the phase transition temperature and electrical resistance increase with the decrease of periods. Especially, the heterojunction [Sb2 Te3 (7 nm)/Ga2 Sb3 (3 nm)]3 film experiences the twice resistance jumps at 208 and 290 °C, respectively, exhibiting the obvious triple-resistance states. The phase structure and vibrational modes of [Sb2 Te3 (7 nm)/Ga2 Sb3 (3 nm)]3 film during the different crystallization stages were observed by the structural characterization. X-ray diffraction and Raman spectroscopy verified the changes in the phase structure and vibrational modes of the film, respectively. The [Sb2 Te3 (7 nm)/Ga2 Sb3 (3 nm)]3 film has a lower surface roughness than the pure Sb2 Te3, which was proved by atomic force microscopy. Phase change memory devices based on the [Sb2 Te3 (7 nm)/Ga2 Sb3 (3 nm)]3 films were fabricated to evaluate the electrical properties and verify the three-state process of the heterostructure. All the results show that the phase-change heterostructure Sb2 Te3 /Ga2 Sb3 films have the potential to achieve triple-state storage by tuning the thickness ratios and periods, which is conducive to improving the information storage density.